2022
DOI: 10.1128/msystems.00651-22
|View full text |Cite
|
Sign up to set email alerts
|

A Metagenomic Investigation of Spatial and Temporal Changes in Sewage Microbiomes across a University Campus

Abstract: Sewage systems harbor extensive microbial diversity, including microbes derived from both human and environmental sources. Studies of the sewage microbiome are useful for monitoring public health and the health of our infrastructure, but the sewage microbiome can be highly variable in ways that are often unresolved.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
5
4
0
Order By: Relevance
“…This study has shown that bacteria such as Proteobacteria, Campylobacterota, Bacteroidota and Firmicutes are relatively highly abundant in WWTP. These findings are consistent with several previous result [ 38 , 39 , 40 ]. In this study, up to 41% of the bacterial sequences were potential animal pathogens, with the most abundant pathogen being the genus Arcobacter in the phylum Campylobacterota, accounting for 6.79% of the total number of sequences.…”
Section: Discussionsupporting
confidence: 94%
“…This study has shown that bacteria such as Proteobacteria, Campylobacterota, Bacteroidota and Firmicutes are relatively highly abundant in WWTP. These findings are consistent with several previous result [ 38 , 39 , 40 ]. In this study, up to 41% of the bacterial sequences were potential animal pathogens, with the most abundant pathogen being the genus Arcobacter in the phylum Campylobacterota, accounting for 6.79% of the total number of sequences.…”
Section: Discussionsupporting
confidence: 94%
“…The many new taxa recovered here by reference-free metagenomics improve the public collections and will potentiate future reference-based metagenomics and sewage monitoring. We found that sewage microbiomes drift apart over time so samples that are temporally close, also have lower beta-diversity confirming expectations and previous findings 13,26 . Surprisingly though, we found striking differences in the impact of seasonality on the surveyed cities.…”
Section: Discussionsupporting
confidence: 91%
“…Since environmental bacteria inherently possess numerous AMR genes, distinguishing the origins of these genes is vital for the focused monitoring of AMR genes associated with human activity. Previous studies have shown that the microbial composition within sewage can exhibit significant variability both temporally and spatially within the same sewage system 13 . In addition, there may be differences in composition and seasonality of microbes across different geographic regions 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Extrapolating this ratio to 100%, their estimation suggests that only 15% of amplicons in a typical sewage sample originate from human stool. However, Fierer et al (2022) found that bacteria derived from fecal material constitute a relatively small fraction of the taxa in collected samples, underscoring the significance of environmental sources in shaping the sewage microbiome. It is still unclear if raw sewage truly reflects the microbial composition of the human gut.…”
Section: Introductionmentioning
confidence: 99%